PEDAGOGIKALIQ TEXNOLOGIYA HÁM INNOVACIYANIŃ RAWAJLANIW TARIYXI - Qazaxbaev, S. (SCIENCE and SOCIETY, 2023)
This article is devoted to the process of inculcation of modern pedagogic technology in to the education system and the assumed results in the process, and also the peculiarities of the practical use of this technology by our teachers.